2016
DOI: 10.1021/acs.iecr.6b03550
|View full text |Cite
|
Sign up to set email alerts
|

A Model to Estimate Heat Efficiency in Steam-Assisted Gravity Drainage by Condensate and Initial Water Flow in Oil Sands

Abstract: Steam-assisted gravity drainage (SAGD) is one of the most popular approaches for oil sands recovery. In this study, an accurate and simple heat efficiency calculation model is presented by modeling transient heat transfer involving the flow of both hot condensate and mobile initial water in oil sands. A 2-D numerical simulation procedure is proposed to calculate temperature distribution ahead of the steam chamber edge in SAGD. A new heat efficiency model is proposed to estimate heat efficiency in SAGD by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Laboratory experiment results have demonstrated that the initial water is mobile when the saturation is above 7% at room temperature [63]. The mobile water outside the steam chamber boundary could significantly impact the growth of the steam chamber [64]. In this work, the effects of the initial water mobility on the SAGD ramp-up phase performance were examined by altering the initial water saturation.…”
Section: Effects Of Initial Water Mobility On the Steam Chamber Ramp-...mentioning
confidence: 99%
“…Laboratory experiment results have demonstrated that the initial water is mobile when the saturation is above 7% at room temperature [63]. The mobile water outside the steam chamber boundary could significantly impact the growth of the steam chamber [64]. In this work, the effects of the initial water mobility on the SAGD ramp-up phase performance were examined by altering the initial water saturation.…”
Section: Effects Of Initial Water Mobility On the Steam Chamber Ramp-...mentioning
confidence: 99%
“…It is known that the most common methods of intensifying oil production from heavy oil and bitumen fields are thermal methods. Hot water injection [3], steam flooding [4,5], cyclic steam stimulation (CSS) [6][7][8], steam-assisted gravity drainage (SAGD) [9][10][11][12], in situ combustion (ISC) [13][14][15][16][17][18][19][20][21], and others are used to develop such fields. For instance, when heavy, highly viscous oils are subjected to steam-thermal treatment at 300 • C, their viscosity decreases significantly.…”
Section: Introductionmentioning
confidence: 99%
“…More than 50% of global oil reserves exist in the form of heavy oil or oil sands [1]. Due to the high viscosity, the heavy oil in the oil layer is usually featured with high flow resistance and sometimes even not able to flow.…”
Section: Introductionmentioning
confidence: 99%